THE IMPACT OF MERGER & ACQUISITION, SHARE BUYBACK, AND DIVIDEND POLICY ON FIRM VALUE CASE STUDY: ENERGY AND MINERAL SECTOR COMPANIES LISTED ON INDONESIA STOCK EXCHANGE IN 2020-2023 - Kaunang, David; Worang, Frederik G.; Tumewu, Ferdinand J. (Universitas Sam Ratulangi, 2024)
This study aims to test the impact of merger & acquisition, share buyback, and dividend policy on firm value case study: energy and mineral sector companies listed on Indonesia Stock Exchange in 2020-2023. This study uses panel data regression in data testing using E-views 12 software, with a population consisting of all energy and mineral sector companies on the Indonesia Stock Exchange. Purposive sampling is the sampling technique used in this study with a sample size of 28 companies. This study results finding that mergers & acquisitions directly no significantly and positively impact on firm value, in contrast with share buyback and dividend policy indicated that directly no significantly and negatively impact on firm value. Keywords: Merger & Acquisition, Share Buyback, Dividend Policy, Firm Value.